Chlorogenic acid ameliorated allergic rhinitis-related symptoms in mice by regulating Th17 cells. Issue 11 (2nd November 2020) - Shi, Zhaohui; Jiang, Weihong; Chen, Xiaodong; Xu, Min; Wang, Jian; Lai, Yubin; Zha, Dingjun
Abstract: Allergic rhinitis (AR) is a non-infectious chronic inflammatory disease of nasal mucosa provoking T helper cell (Th) 17 response. Chlorogenic acid (CGA), one of the most abundant polyphenol compounds in various agricultural products, possesses antiviral, anti-inflammatory, and antibacterial properties. However, the effect of CGA on AR is unclear. Thus, our study explored the effect of CGA in modulating AR-related symptoms and immunoreaction, especially Th17 response. AR mice were induced by ovalbumin (OVA) administration and further treated with CGA or dexamethasone (Dex). The frequencies of rubbing and sneezing of AR mice were recorded. Histopathological analysis of nasal mucosa was conducted by Hematoxylin–Eosin and Periodic acid–Schiff stainings. The serum and nasal mucosa levels of OVA-immunoglobulin (Ig)E, interferon (IFN)-γ, retinoic acid-associated nuclear orphan receptor (ROR)-γt, and interleukin (IL)-17A were measured by enzyme-linked immunosorbent assay, quantitative reverse-transcription polymerase chain reaction (qRT-PCR), or Western blot. The ratio of CD4 + IL-17 + Th17 cells to CD4 + T cells in peripheral blood of AR mice was assessed by flow cytometer. CGA diminished the frequencies of rubbing and sneezing of AR mice in a concentration-dependent manner. CGA attenuated histopathological abnormalities and decreased goblet cell number in nasal mucosa of AR mice. CGA decreased the serum levels of OVA-IgE, ROR-γt, and IL-17A, while increasing the serum level of IFN-γ in AR mice. Meanwhile, CGA decreased the ratio of CD4 + IL-17 + Th17 cells to CD4 + T cells in peripheral blood and the mRNA and protein levels of IL-17A and ROR-γt in AR mice. CGA ameliorated AR-related symptoms in mice by regulating Th17 cells, which could be a candidate for the treatment of AR.